(untitled) (Journal of Comparative Social Work, 2008)
More than ever social workers have to face people from cultures other than their own. How can this professional group best meet the multicultural reality of today’s society? It is in the social work study programs that the basis is laid for good cultural understanding in social work practice. It is also there that the basis is laid for social workers to orientate their work towards cultural processes that are relevant to the welfare situation of people.